Testing of the hypotheses of the renewal process under local asymptotic normality - Kanišauskas, Vaidotas (Lietuvos matematikos rinkinys, 2025)
The paper deals with a statistical experiment induced by a renewal process with a continuous compensator. Given the local asymptotic normality of probability measures, the asymptotically locally most powerful criteria for testing the simple hypothesis with the complex parametric alternative are found. It is also shown how these hypotheses are practically tested with specific data.
Keywords: renewal process; local asymptotic normality; asymptotically locally most powerful test